1 Day Consultancy and Training on Excel for Data Driven Decision - Siti Roslindar, Yaziz (2023)
UMP Paya Besar, 7 Jan. 2023 – The Centre for Mathematical Sciences has successfully organised a 1-day consultancy and training on Excel for Data-Driven Decision for the staff of Najeehah International Sdn. Bhd. at Wisma Najeehah, Kota Bharu, Kelantan.